2013
DOI: 10.1136/amiajnl-2013-001930
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative approach to developing an electronic health record phenotyping algorithm for drug-induced liver injury

Abstract: Phenotyping algorithms developed for rare and complex conditions are likely to require adaptive implementation at multiple institutions. Better approaches are also needed to share algorithms. Early agreement on goals, data sources, and validation methods may improve the portability of the algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…Therefore, additional studies in other EMR databases are needed to confirm the optimal search strategy. The results of our study are similar to those of Overby et al who used a more complex computerized algorithm involving hierarchical searching methods 11 . In their study, a series of liver injury terms that were initially developed in a retrospective dataset of EMR's were shown to perform with a high degree of sensitivity and specificity for DILI cases in a prospective manner.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, additional studies in other EMR databases are needed to confirm the optimal search strategy. The results of our study are similar to those of Overby et al who used a more complex computerized algorithm involving hierarchical searching methods 11 . In their study, a series of liver injury terms that were initially developed in a retrospective dataset of EMR's were shown to perform with a high degree of sensitivity and specificity for DILI cases in a prospective manner.…”
Section: Discussionsupporting
confidence: 89%
“…Investigators have used a variety of methods to search computerized EMR and administrative databases for potential DILI cases with varying success 8-11 . In the current study, a novel text searching method was developed to peruse a large number of outpatient and ER encounters contained in a widely used commercial EMR product (EPIC) at a large tertiary care center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The incorporation of laboratory, pharmacy, and pathology data hold even greater promise in improving the yield of these electronic searching strategies. 17 In the study by Re et al, 7 a series of surrogate ICD-9 codes for presumed DILI were used followed by an "expert opinion Q10 " review of 298 individual charts that met the laboratory criteria for potential ALF. Of note, the authors previously reported on the poor performance of various ICD-9 codes to identify ALF patients in the same data set.…”
Section: Q8mentioning
confidence: 99%
“…Examples of the combined use of standard NLP and text-and data-mining are found in [139][140][141] where cTAKES is used with Boolean logic to perform phenotyping and to extract drug-side effects. MedLEE was applied for: 1) adverse drug reaction (ADR) signaling, where the association between a drug and an ADR was obtained by using disproportionality analysis [142,143] or Boolean logic [144], or by building and analyzing statistical distributions of concepts (i.e., diseases, symptoms, medications) extracted from the narrative text [145]; 2) EHR-data driven phenotyping using Boolean logic on MedLEE-extracted concepts [136,146]; 3) automated classification of outcomes from the analysis of emergency department computed tomography imaging reports using machine learning methods, such as decision trees [147]. MetaMap has been used with logistic regression in [148] to discover inappropriate use of emergency room based on information on drugs, psychological characteristics, diagnoses, and symptoms.…”
Section: F Extraction Of Information From Unstructured Clinical Datamentioning
confidence: 99%